PEDAGOGICAL MODEL FOR THE INTEGRATION OF EDUCATIONAL MAPS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Boyarinov, Dmitry (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The processes of digitalization of all aspects of social life are also completely manifested in the field of education. The most comprehensive form of digitalization in education is the digital educational environment. The purpose of our study: to develop a pedagogical model for the integration of educational maps in that environment.The problems of analyzing modern approaches to building a digital educational environment and determining its structure, identifying the didactic properties of educational maps, as a structural element of such an environment are considered in the article. The digital educational environment should provide support for collective forms of learning and contain a continuously operating system of information interaction between students and teachers which allows flexible change of scenarios of that interaction. It is indicated accordingly that the digital educational environment should provide equal access rights for the student and teacher to the information and the ability to quickly restructure educational maps when the content of educational material changes. Two main scenarios of the functioning of the digital educational environment with integrated educational maps - synchronous and asynchronous are discussed in the article and a system of quality criteria for assessing the effectiveness of the functioning of that environment is proposed.